Performing Muslim identities through embodiment: Self-representing through fashion, aesthetics, and style - Bernier, Asma (The Motley Undergraduate Journal, 2023)
Modesty is practiced by people regardless of their class, sexuality, gender, race, or religion. However, there is an association between modesty, Islam, and the Islamic veil (or hijab). Hijab is an Islamic garment that is meant for Muslim women to wear if they choose to do so. Vast interpretations of Islamic texts produce variability in the definitions and understandings surrounding modesty. Veiled Muslim women practice modesty by concealing their hair, skin, and body. The veil is a signifier of their religious affiliation and modest lifestyle. This paper is a study of performance and visual enactment within the photos and videos posted by a sample of veiled Muslim women influencers, which include Nawal Sari and Rawdah Mohamed. Hijabi influencers, or hijabistas, are veiled Muslim women who are consistent with fashion trends and hijab styles in an online context. This article uses visual rhetorical analysis to examine the captions and the clothing, pose, background, symbols, colours and textures present in the photos and videos. By doing this, this paper seeks to examine how hijabi influencers define Islamic modesty through the photos and videos uploaded on their visual social media platforms. Theoretical frameworks, such as post-colonial feminism, orientalism, and creative labour support the interpretation of the data. This research demonstrates that the definition of Islamic modesty can be understood beyond a binary perspective.